DETERMINAN PROFIT GROWTH PADA PERBANKAN INDONESIA - Alexander Raphael Hasibuan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
Getting profit is the basic goal of every company, therefore every company strives to optimize business then profit growth is positive. The purpose of this study was to determine the effect of financial performance, differences in accounting profit and fiscal profit on Profit Growth in banking companies listed on the Indonesia Stock Exchange. This study uses descriptive quantitative methods. Sample selection is done by purposive sampling method. There are 11 companies that meet the criteria as research samples so that there are 55 financial statements analyzed using descriptive statistical tests and multiple linear regression analysis models using the SPSS program (Statistical Package for Social Science) v.23. The results of the study show Net profit margin, permanent differences and temporary differences have an effect on simultaneously on profit growth. Keywords: Net Profit Margin, Permanent & Temporary difference, Profit Growth